PENGARUH PENILAIAN PRESTASI KERJA TERHADAP KEPUASAN KARYAWAN BAGIAN UMUM PADA PT. PERKEBUNAN NUSANTARAV (PERSERO) PEKANBARU - Gracesy Rebecca; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The problems that arise in this study assumed are the low employee’s satisfaction at the Center Office PT. PTPN V (Persero) Pekanbaru showed the turnover absenteeism that fluktuatif. The problems be important because could become threat to objectif of vision and mission of PTPN V. It should be solved immediately.This research aims to know how is the description about performance appraisal and the description of employee’s satisfaction and how is the impact of performance appraisal towards employee satisfaction at the office PT. PTPN V (Persero) Pekanbaru.This research uses survey method with the population number is 78 employees. And then, the sample that as many as 78 respondents from the population. The questionnaire taken is likert scale questionnaire model. And analysis model applied is a simple linear regression, the coefficient of determination and test T.The results showed that the performance appraisal has an impact an employee satisfaction by 34.6%. Therefore, author suggest is the best implementation of the assesment focuses more on work achievement values objectiveness so employees will feel satisfaction with the result that match their accomplishment, because the performance appraisal has a fairly strong influence on employee satisfaction.Keywords : Performance Appraisal, Employee’s Satisfaction